Hemorrhage and complications associated with percutaneous ultrasound guided liver biopsy in dogs - Reece, Jonjo (J Vet Intern Med, 2020)
BACKGROUND: Liver biopsy is often necessary to obtain a diagnosis in dogs with hepatobiliary disease. Hemorrhage after biopsy is a concern. OBJECTIVE: To describe the extent of hemorrhage and incidence of complications after percutaneous ultrasound guided liver biopsy (PUGLB) in dogs and to examine risk factors for hemorrhage or complications. ANIMALS: One hundred two client owned dogs with suspected hepatobiliary disease that underwent PUGLB. METHODS: Medical records were retrospectively reviewed. Using human guidelines, major hemorrhage was defined as an absolute decrease in the PCV (ΔPCV) ≥ 6%. Complications were defined separately as clinically relevant physiologic compromise that necessitated intervention or death. The relationship between ΔPCV and the occurrence of complications and the initial PCV, coagulation variables, serum activity of liver‐derived enzymes, serum bilirubin concentration, number of biopsies, biopsy needle gauge, radiologist experience, histological diagnosis, and ultrasound variables were compared. RESULTS: Before PUGLB, most aberrations in coagulation variables were mild. After biopsy a decrease in PCV occurred in 87/102 (85.3%) dogs. The mean ΔPCV was −7.2% ± 4.5%. Major hemorrhage occurred in 43/102 (42.2%) dogs and complications in 2/102 (1.9%). ΔPCV was significantly positively correlated with PCV before biopsy (r = .47, P = .004). There was no correlation between ΔPCV or complications with any of the variables examined. CONCLUSION AND CLINICAL IMPORTANCE: Percutaneous ultrasound guided liver biopsy in the population of dogs in the current study, with normal or mild abnormalities in coagulation, results in a high incidence of clinically silent, major hemorrhage (42.5%), but few complications (1.9%).